Methodical guidance self-studying and individual task performance from course "International Cooperation and Grant Writing in Environmental Protection" - Tykhomyrova, T. S.; Babenko, V. M.; Kriuchkova, V. V. (National Technical University "Kharkiv Polytechnic Institute", 2024)
Self-studying, which involves studying without direct supervision or attendance in a classroom, is a valuable way to learn more and get deep knowledge is any discipline. Interational cooperation is essential to ensure support and progress in the development of coordinated global efforts on sustainable water and energy solutions and to create awareness and disseminate knowledge on the advantages of such integrated approach. International cooperation can help establish common standards and practices for sustainable production and consumption, and provide adequate avenues for SIDS to develop the capacity to become major players with respect to the circular economy.
Методичні вказівки до самостійної роботи студентів та виконання індивідуального завдання з дисципліни "Міжнародна співпраця та грантрайтинг в екології"
Keywords: methodical guidance; self-studying; individual task performance; international cooperation and grant writing in environmental protection